1992
DOI: 10.2527/1992.70103044x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of real-time ultrasound technology for predicting fat thicknesses, longissimus muscle areas, and composition of Brangus bulls from 4 months to 2 years of age

Abstract: Sixty Brangus bulls were evaluated live using two real-time ultrasound instruments and four technicians to estimate longissimus muscle area (LMA) and 12th rib fat thickness (FT) every 4 mo beginning at 4 and 12 mo of age, respectively, and continuing until 24 mo of age. Ten bulls were slaughtered every 4 mo to determine actual LMA and FT, 9-10-11th rib chemical composition, yield grade (YG) factors, and empty body weight (EBW). Live animal traits were used to predict 9-10-11th rib composition, YG, and EBW. Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
3
25

Year Published

1993
1993
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 7 publications
6
23
3
25
Order By: Relevance
“…They also concluded that scanned measurements estimated carcass yield percentage as accurately as the same measurements taken on the carcass. A similar conclusion was also reached by Faulkner et al (1990), Miller et al (1988), Waldner et al (1992) and Williams et al (1997).…”
Section: Introductionsupporting
confidence: 71%
“…They also concluded that scanned measurements estimated carcass yield percentage as accurately as the same measurements taken on the carcass. A similar conclusion was also reached by Faulkner et al (1990), Miller et al (1988), Waldner et al (1992) and Williams et al (1997).…”
Section: Introductionsupporting
confidence: 71%
“…Although some reports show a decrease in accuracy as FT values increase, accuracy increases as cattle approach slaughtering due to a small weight gain variation among animals. Further, the highest carcass FT value found in this study was 7.04 mm for Angus crosses, whereas accuracy starts to be impaired when FT values are higher than 10 mm (Faulkner et al, 1990;Perkins et al, 1992a;Waldner et al, 1992;Bergen et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonography is emphasized within this context as a viable (Frost et al, 1997), reliable and acceptable costeffective technique (Houghton & Turlington, 1992). Ultrasound live measurements can be utilized to estimate muscle growth, predict carcass composition (Bailey et al, 1986;Faulkner et al, 1990;Perry & Fox, 1997;Renand & Fisher, 1997) and yield of commercial meat cuts (Waldner et al, 1992;Hassen et al, 1999b), as well as to estimate animal body condition score and nutritional status (Busboom et al, 2000). Live measurements are taken from the Longissimus dorsi muscle section area (REA), and from the backfat layer thickness (FT) in the same muscle, based on images made between the 12 th and 13 th ribs.…”
Section: Introductionmentioning
confidence: 99%
“…As diferenças entre as avaliações na carcaça e por ultrassom dependem da experiência do técnico, das mudanças post mortem, da espessura do couro, do comprimento do pelo, do nível de acabamento, entre outros fatores (Waldner et al, 1992). Entretanto, Waldner et al (1992) avaliaram a utilização do ultrassom em bovinos da raça Brangus em diversos períodos de abate -com as medidas realizadas por vários operadores com diferentes níveis de experiência -e afirmaram que as medidas de área de olho-de-lombo foram subestimadas por todos os operadores, independentemente do nível de experiência, quando a área de olho-de-lombo foi menor que 70 cm 2 . Neste trabalho a área de olho-de-lombo, em todos os períodos de confinamento, foi menor que 70 cm 2 (Tabela 2), confirmando que área de olho-de-lombo menor que 70 cm 2 medida por ultrassom subestima as medidas da carcaça.…”
Section: Resultsunclassified